Manajemen Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di Madrasah Ibtidaiyah Negeri (MIN) - Elviana Sinaga; Yunita Sipahutar; Syanty Ericka; Ismi Yulizar (Jurnal Zeniusi, 2026)
This study aims to examine the management of school leadership in improving teacher performance at Madrasah Ibtidaiyah Negeri (MIN). This research uses a descriptive qualitative approach with the subjects being the school principal and MIN teachers. Data collection techniques were carried out thru interviews, observations, and document studies. Data analysis was conducted thru the stages of data reduction, data presentation, and conclusion drawing, while data validity was ensured thru source and technique triangulation. The research results show that the management of the principal's leadership is carried out thru targeted work program planning, proportional organization of teachers' tasks, participatory leadership implementation, and supervision thru continuous academic supervision. In addition, the principal also provides continuous motivation, guidance, and coaching to the teachers. Communicative and humanistic leadership can enhance teachers' motivation, discipline, and responsibility in carrying out their professional duties. The conclusion of this research shows that the management of school principal leadership plays an important role in improving the performance of teachers at Madrasah Ibtidaiyah Negeri (MIN). Effective and sustainable leadership is the main factor in creating a conducive work environment and improving the quality of education in madrasahs.